2017
DOI: 10.1159/000486222
|View full text |Cite
|
Sign up to set email alerts
|

Chloroquine Enhances the Radiosensitivity of Bladder Cancer Cells by Inhibiting Autophagy and Activating Apoptosis

Abstract: Background/Aims: Chloroquine was formerly used as an anti-malarial agent drug but has now been proven to be useful for various diseases. This study aimed to investigate the radiosensitizing effect of chloroquine in bladder cancer, with an emphasis on autophagy inhibition and apoptosis induction. Methods: Bladder cancer cell lines were irradiated with or without chloroquine. Cell proliferation was determined by a Cell Counting Kit 8 assay. The radiosensitization effect of chloroquine was evaluated by clonogenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 36 publications
(45 reference statements)
2
56
0
1
Order By: Relevance
“…They are believed to inhibit lysosome-dependent autophagy and improve chemo and radio sensitivity [76]. Some of the most recent publications on this matter included breast cancer [77], pancreatic cancer [78,79], lung cancer [80], colon cancer [81], and bladder cancer [82].…”
Section: Quinolines: Chloroquine and Quinidinementioning
confidence: 99%
“…They are believed to inhibit lysosome-dependent autophagy and improve chemo and radio sensitivity [76]. Some of the most recent publications on this matter included breast cancer [77], pancreatic cancer [78,79], lung cancer [80], colon cancer [81], and bladder cancer [82].…”
Section: Quinolines: Chloroquine and Quinidinementioning
confidence: 99%
“…To overcome radioresistance and increase survival, many attempts have been made to develop new radiosensitizers [15][16][17][18]. Recent studies revealed that ultrasound-stimulated microbubbles (USMBs) induced vessel destruction in tumors [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, more and more evidences have con rmed the existence of autophagy is the basic mechanism of cell survival in stressful environments caused by radiotherapy and chemotherapy. The increase of autophagy will enhance the radioresistance of tumor, and tumor with autophagy defect are more sensitive to radiotherapy [45].…”
Section: Discussionmentioning
confidence: 99%